The Effect of Social Support and Hope on Resilience in Adolescents - Novi Hidayat; Siti Rohmah Nurhayati (Humaniora, 2019)
This study intended to investigate the effect of social support and hope simultaneously and independently on resilience in adolescents. This study used quantitative methods with ex post facto design. Multistage random sampling techniques were used, which resulted in a sample of 291 adolescents in junior high school from Pagentan district, Central Java, Indonesia. They completed three questionnaires of social support, hope, and resilience. The validity of the instruments used was measured by psychology measurement experts (content validity). Then, the reliability of the instruments was analyzed using Cronbach’s alpha. The Cronbach’s alpha for each instrument was 0,854 (social support), 0,835 (hope), and 0,778 (resiliency). Data were analyzed using multiple regression at the significance level of 0,05. The results of the study reveal that there is an effect of social support and hope simultaneously and independently on resilience in adolescents. There are effective contributions of social support and hope to the resilience of about 41% (from social support 13,2% and hope of 27,8% respectively).